2020
DOI: 10.3390/ijerph17124518
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status Is Related to Health-Related Physical Fitness and Physical Activity but Not to Sedentary Behaviour in Children

Abstract: Purpose: The aim of this research was to describe, examine, and compare the level of physical fitness, physical activity, and sedentary behaviour in pupils aged 6–13 in the Region of Murcia, Spain, in accordance with weight status. Methods: A total of 370 children (166 girls and 204 boys) aged 6–13 (M = 8.7; DT = 1.8) from the Region of Murcia participated in this descriptive and cross-sectional study. Some anthropometric parameters such as body mass index, waist circumference, as well as skinfold measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
2
6
0
6
Order By: Relevance
“…Regarding body weight, a statistically significant negative correlation was found with CRF. This finding is in agreement with other studies [ 29 , 30 ]. The correlation between children's height and CRF was statistically negatively significant, in contrast to what other studies suggest [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding body weight, a statistically significant negative correlation was found with CRF. This finding is in agreement with other studies [ 29 , 30 ]. The correlation between children's height and CRF was statistically negatively significant, in contrast to what other studies suggest [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Meanwhile, muscular strength and flexibility were not shown to significantly affect obesity-related factors in intellectually disabled people. These results are similar to those of previous studies, which found a static correlation between weight and muscle strength [ 48 , 49 ]. Muscular strength is defined as the ability of a muscle to exert maximum contractile force at once, against resistance [ 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Physical activity in leisure time could have mediated effects of soccer and multisport activities on physical fitness and motor coordination, hence, the lack of physical activity monitoring in leisure time is another limitation, whose influence must be controlled and evaluated in future studies. López-Gil et al recently showed that children with normal weight achieved higher results for health-related physical fitness [42], therefore the fact that we did not control the soccer and multisport activities' effects on physical fitness for weight status could be acknowledged as a limitation as well. Moreover, the lack of information on how long participants have been engaged in soccer or multisport programs is considered a limitation due to the fact that this could affect the results.…”
Section: Discussionmentioning
confidence: 95%